PPI-responsive esophageal eosinophilia and eosinophilic esophagitis: More similarities than differences - Eluri, Swathi (Curr Opin Gastroenterol, 2015)
PURPOSE OF REVIEW: To discuss the clinical, endoscopic, and histologic features, pathogenesis, and disease mechanisms of proton pump inhibitor–responsive esophageal eosinophilia (PPI-REE), and to highlight similarities and differences with eosinophilic esophagitis (EoE). RECENT FINDINGS: PPI-REE is a condition in which patients have clinical and histologic findings similar to EoE, but achieve complete remission with proton pump inhibitor (PPI) treatment. More than one-third of patients who have esophageal symptoms associated with esophageal eosinophilia respond to PPI treatment. Emerging data elucidating the pathogenesis of PPI-REE have shown that Th2-related inflammatory factors such as IL-13, IL-5, eotaxin-3, and major basic protein (MBP) are elevated in PPI-REE, similar to EoE. PPI-REE also shares a genetic expression signature with EoE that reverses with PPI treatment. Mechanisms proposed to explain the PPI response include an acid-independent, anti-inflammatory action of PPIs and PPI-induced restoration of esophageal barrier function. SUMMARY: Multiple features of PPI-REE overlap extensively with EoE. This raises the question of whether PPI-REE is merely a subtype of EoE rather than an independent condition. This similarity may have future implications for algorithms informing evaluation and treatment of esophageal eosinophilia.